x-7.(-9)x-15
27x - 5y
-11
19x = 437 x = 437 ÷ 19 x = 23
19x = 437 x = 437 ÷ 19 x = 23
If you mean 4x-19x=50 then x = -3 1/3 or -10/3... Here's how I did it. 4x-19x=50 (4-19=-15) -15x=50 (// -15; divide both sides by -15) x=-50/15 (simplify) x=-10/3 or -3 1/3 If you have any more questions with math related stuff ask away right here (http://www.tutorjam.com/subjects/math_programs.html)!!
x^2-19x+90 (x-9) (x-10)
8x - 7 = 15 + 19xsubtract 19x from both sidesadd seven to both sides8x -19x = 15 +7-11x = 22divide both sides by -11x = -2
152
19x
3
-19x/38xy = -1x0/y = -1/y
The given expression is 5x + 2y + 19x - 2y - 1. To simplify this expression, we combine like terms. Combining the x terms gives us 24x (5x + 19x) and combining the y terms gives us 0y (2y - 2y). Therefore, the simplified expression is 24x - 1.